(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Lower gastrointestinal bleeding (LGIB) is defined as bleeding from a source below the ligament of Treitz. Most series which studied the etiology of the acute LGIB showed that Colonic diverticulae and angiodysplasia were the commonest etiology identified, ranging from (17- 40%, 2-30% respectively). Colitis including the inflammatory bowel disease, account for 6-30% of cases. Uncommon causes of LGIB include colonic neoplasia in 11-14% and anorectal lesions in 4-10% (mostly due to hemorrhoids,). Other less common cause is small bowel source in 2-9%; rare causes include Dieulafoy lesion and colonic ulcerations. Objective:To verify the etiology of LGIB in Iraqi patients. Methods:The study group included 100 patients who were suffering from acute lower gastrointestinal bleeding and referred to the endoscopy unit in the Gastroenterology and Hepatology Teaching Hospital. After the initial history, physical examination and laboratory studies were obtained; all patients with hemodynamic instability were resuscitated with intravenous fluid and blood transfusion. Colonoscopy performed within 12 hours of hospitalization (with or without an upper endoscopy), with the aim of reaching up to the cecum in all cases. Results:Of 100 patients (55 female, 45 male) 78% presented with haematochesia, 11% with red maroon stool with malaena, and 11% with malaena only. Bleeding due to colitis was the most frequent diagnosis, which is reported in 38 patients. The diagnosis of anorectal lesions and colonic neoplasia were the second and third most common diagnosis (21%, 12% respectively). Colonic diverticulae in 12 patients, colonic angiodysplasia in 11 patients and small intestinal source is 5 patients and 1 patient with colonic Dieulafoy lesion. Conclusions:This study showed that inflammatory bowel disease; colorectal polyps including post polypectomy bleeding, diverticulosis, angiodysplasia, and hemorrhoids were the most common causes of lower gastrointestinal bleeding. Key words:Lower gastrointestinal bleeding